Penerapan Inovasi Jus Kacang Hijau dan Jambu Biji untuk Meningkatan Kadar Hemoglobin pada Ibu Hamil Anemia Trimester III di PMB Umi Muntamah - Tria Susanti; Eti Sulastri (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2019)
Implementing the application of green bean juice and guava in pregnant women with anemia TM III at Umi Muntamah Sruweng PMB. This study was descriptive analytic, with a case study approached. Data were obtained through direct observation. Result: after being given participants' green bean juice and red guava juice for 14 days, there was an increase in Hemoglobin, ie 10.7g / dL to 13 g / dL (participant 1), 8.5 g / dL to 12.2 g/dL( participant 2), 9.6 g / to 12.1 g / dL (participant 3), 8.6 g / dL to 11.7, and 9.7 g / dL to 12.2 g / dl. Giving green bean juice and guava juice have been applied by the five participants, it was given in the afternoon and evening as a companion fe tablet in 14 days. The five participants experienced an increase in HB levels from anemia to not be anemic. There was a change in Hemoglobin levels after consuming green bean juice and red guava juice that the mother with anemia became not anamic.